2021
DOI: 10.47278/journal.ijvs/2020.030
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Histological, Histochemical and Ultrastructure Studies on the Exocrine Pancreas of Japanese Quail (Coturnix coturnix japonica) and Cattle Egret (Bubulcus ibis)

Abstract: The current study targeted to compare between the pancreas (exocrine part) of Japanese quail and Cattle egret. The pancreas was investigated in eight apparent healthy mature female Japanese quail and eight Cattle egret. Histological, histochemical, and ultrastructure studies were carried out. In both birds, the pancreas is located on the right side of the abdomen between the ascending and descending loops of the duodenum. The pancreas of the Japanese quail composed of dorsal, ventral, third, and splenic lobes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…According to the reported results, the macroscopic and microscopic characteristics of the pancreas can be widely different between avian species regarding its lobe number, type and distribution of islets, type of endocrine cells in islets and pancreatic duct number and structure. For instance, it has been reported that, despite other avian species, the pancreas in the cattle egret is not lobulated (Yehia et al., 2021). Or in microscopic structure, usually the ductal system begins with centroacinar cell, however, it was reported that this cell was absent in the Guinea fowl, common gull (Hamodi et al., 2013) and mynah (Saadatfar & Asadian, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…According to the reported results, the macroscopic and microscopic characteristics of the pancreas can be widely different between avian species regarding its lobe number, type and distribution of islets, type of endocrine cells in islets and pancreatic duct number and structure. For instance, it has been reported that, despite other avian species, the pancreas in the cattle egret is not lobulated (Yehia et al., 2021). Or in microscopic structure, usually the ductal system begins with centroacinar cell, however, it was reported that this cell was absent in the Guinea fowl, common gull (Hamodi et al., 2013) and mynah (Saadatfar & Asadian, 2009).…”
Section: Introductionmentioning
confidence: 99%